2013
DOI: 10.1021/am403071k
|View full text |Cite
|
Sign up to set email alerts
|

Infrared-Actuated Recovery of Polyurethane Filled by Reduced Graphene Oxide/Carbon Nanotube Hybrids with High Energy Density

Abstract: Optically actuated shape recovery materials receive much interest because of their great ability to control the creation of mechanical motion remotely and precisely. An infrared (IR) triggered actuator based on shape recovery was fabricated using polyurethane (TPU) incorporated by sulfonated reduced graphene oxide (SRGO)/sulfonated carbon nanotube (SCNT) hybrid nanofillers. Interconnected SRGO/SCNT hybrid nanofillers at a low weight loading of 1% dispersed in TPU showed good IR absorption and improved the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 50 publications
1
56
1
4
Order By: Relevance
“…Recently, graphene oxide, graphene, and graphene nanoplates have been shown to be even more advantageous than carbon nanotubes, [7][8][9][10][11][12][13] especially for their uses in polymer composites with high thermal conductivity. [14,15] Hexagonal boron nitride (BN) is structurally analogous to graphite and has equally good thermal transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, graphene oxide, graphene, and graphene nanoplates have been shown to be even more advantageous than carbon nanotubes, [7][8][9][10][11][12][13] especially for their uses in polymer composites with high thermal conductivity. [14,15] Hexagonal boron nitride (BN) is structurally analogous to graphite and has equally good thermal transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al reported the formation of mechanically improved and thermally stable reduced graphene nanoribbon/CNT/TPU nanocomposites, which involved complicated hybrid preparatory method through unzipping the MWCNTs . In another work, the fabrication of sulfonated reduced graphene oxide (GO)/sulfonated carbon nanotube/TPU nanocomposites is reported for IR‐actuated shape recovery applications . Motivated by these, we have concentrated our work on preparation of hybrid by simple methods in quest of developing TPU nanocomposites even with much superior properties.…”
Section: Introductionmentioning
confidence: 99%
“…These unique properties of graphene have been used to produce different multi-stimuli responsive SMPs. Infrared light actuated SMPs are a class of these materials and some studies have been done in this regard [17,37,38]. Kashif et al [37] have produced shape memory polyolefin elastomer/modified graphene nanocomposites responding to infrared light with healing properties.…”
Section: Introductionmentioning
confidence: 99%
“…Kashif et al [37] have produced shape memory polyolefin elastomer/modified graphene nanocomposites responding to infrared light with healing properties. Feng et al [38] have prepared IR actuated shape memory polyurethane with the aid of reduced graphene oxide and carbon nanotube hybrids. Park and Kim [17] have studied on the semi-crystalline poly urethane/graphene shape memory nanocomposite system responding to infrared light.…”
Section: Introductionmentioning
confidence: 99%